Robotics and Mechatronics Proceedings of the Fifth IFToMM International Symposium on Robotics & Mechatronics (ISRM 2017) - (Chunhui) Yang, Richard; Takeda, Yukio; Zhang, Chunwei; Fang, Gu (Mechanisms and Machine Science,, 2019)
This book gathers the proceedings of the ISRM 2017, the fifth IFToMM International Symposium on Robotics and Mechatronics, which was jointly organised by the School of Computing, Engineering and Mathematics at Western Sydney University, Australia and by the IFToMM Technical Committee on Robotics and Mechatronics. The respective contributions showcase the latest advances, trends and future challenges in Computer Modelling and Simulation, Kinematics and Dynamics of Multi-Body Systems, Advanced Dynamics and Control Methods, Linkages and Mechanical Controls, Parallel Manipulators, Mechanism Design, Sensors and Actuators, Mobile Robotics: Navigation and Motion Planning, Bio-inspired Robotics, Micro/Nano-Robotics and Complex Robotic Systems. .